Contribution of animal studies to migraine research. Issue 3 (15th December 2019) - Shibata, Mamoru
Abstract: The pathophysiology of migraine is still largely unknown. Since migraine is a paroxysmal functional disorder without established biomarkers, it is extremely hard to capture migraine‐related abnormalities in a tangible manner. There have been numerous attempts to recapitulate disease processes relevant to migraine using animal disease models. By combining scientific data from human studies with those from animal experiments, researchers have been trying to elucidate the pathophysiology of migraine little by little, and such endeavors also contributed to the development of novel therapy. In the past, migraine was considered purely as a vascular disease. However, histological studies on trigeminal nerves innervating the cranial structures in combination with the discovery of neuropeptides, such as calcitonin gene‐related peptide (CGRP), and the trigeminal fibers innervating the dura mater were found to play a pivotal role in the development of headache. Cortical spreading depolarization/depression (CSD) is defined as a wave of abrupt and sustained near‐complete breakdown of transmembrane ion gradient and mass depolarization concentrically spreading at ∼2‐3 mm/min in the genetic mutations relevant to familial hemiplegic migraine illustrated the importance of ion homeostasis in determining the threshold of CSD occurrence and the metabolic burden on the brain tissue incurred from CSD. In typical migraine aura attacks, aura is experienced prior to the headache phase. Animal studies have provided scientific basis that explains this unique temporal relationship between aura and headache. Despite many limitations, there is no doubt that animal experiments are indispensable for advancing migraine research.